2020
DOI: 10.3390/min10020147
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Substitutions of Minor and Trace Elements in Co-Existing Sphalerite and Wurtzite

Abstract: The nature of couple substitutions of minor and trace element chemistry of expitaxial intergrowths of wurtzite and sphalerite are reported. EPMA and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) analyses display significant differences in the bulk chemistries of the two epitaxial intergrowth samples studied. The sample from the Animas-Chocaya Mine complex of Bolivia is Fe-rich with mean Fe levels of 4.8 wt% for wurztite-2H and 2.3 wt% for the sphalerite component, while the sample fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Previous studies on the concentration of high-tech metals in deposits from the Bolivian tin belt have focused mostly on the sulfide mineralization (Schwarz-Schampera and Herzig 2002;Ishihara et al 2011;Artiaga et al 2013;Murakami and Ishihara 2013;Jiménez-Franco et al 2018;Cacho et al 2019;Torres et al 2019;Torró et al 2019a,b;Pring et al 2020; summary of reported maximum concentrations of In, Ge and Ga shown in Table 3). In the following lines we assess the potential of cassiterite from the Bolivian tin belt as a source of high-tech, critical elements, chiefly Nb, Ta, In, Ge and Ga, by comparing our results with bibliographic values.…”
Section: Potential Of Cassiterite From the Bolivian Tin Belt As A Source Of Critical Elements As Byproductsmentioning
confidence: 99%
“…Previous studies on the concentration of high-tech metals in deposits from the Bolivian tin belt have focused mostly on the sulfide mineralization (Schwarz-Schampera and Herzig 2002;Ishihara et al 2011;Artiaga et al 2013;Murakami and Ishihara 2013;Jiménez-Franco et al 2018;Cacho et al 2019;Torres et al 2019;Torró et al 2019a,b;Pring et al 2020; summary of reported maximum concentrations of In, Ge and Ga shown in Table 3). In the following lines we assess the potential of cassiterite from the Bolivian tin belt as a source of high-tech, critical elements, chiefly Nb, Ta, In, Ge and Ga, by comparing our results with bibliographic values.…”
Section: Potential Of Cassiterite From the Bolivian Tin Belt As A Source Of Critical Elements As Byproductsmentioning
confidence: 99%
“…The Merelani sphalerite and wurtzite are Mn-rich, and were found to contain several trace elements (e.g., Fe, Cu, Se, and Cd) with concentrations greater than 500 ppm and a discernable differentiation between the sphalerite and wurtzite. Noteworthy, 1450 ppm Ga in the wurtzite and 1750 ppm in the sphalerite phases were also reported [8], with estimated standard deviations of 30 and 80 ppm, respectively. In both the sphalerite and wurtzite phases, trace Ga and Cu concentrations were consistent with the coupled substitution Cu + + Ga 3+ ↔ 2Zn 2+ .…”
Section: Introductionmentioning
confidence: 86%
“…The mines are also host to well-formed and uncommonly large crystals of pyrite, alabandite, and wurtzite as well as several rare sulfides, including clausthalite (PbSe), germanocolusite (Cu 13 VGe 3 S 16 ), and merelaniite (Mo 4 Pb 4 VSbS 15 ) [5][6][7]. A detailed study of the chemistry of intergrown sphalerite and wurtzite, which included samples the Merelani mines and from the Animas-Chocaya Mine complex, Quechisla district, Bolivia, was recently published [8]. The Merelani sphalerite and wurtzite are Mn-rich, and were found to contain several trace elements (e.g., Fe, Cu, Se, and Cd) with concentrations greater than 500 ppm and a discernable differentiation between the sphalerite and wurtzite.…”
Section: Introductionmentioning
confidence: 99%
“…Both forms of ZnS are important in mineralogy as many minerals crystallise in the same structures. For example, there are würtzite and spha-lerite forms of AgI (iodargyrite and miersite) and CdS (greenockite and hawleyite) [109]. Most of our gas vapour transport and salt flux experiments led to the formation of pure cubic sphalerite.…”
Section: Geochemistry Of Au In Sulphidesmentioning
confidence: 97%